CONTENT OF FINANCIAL EVALUATION OF INVESTMENT PROJECT CAPITAL AT THE COMMERCIAL BANK FOR INVESTMENT AND DEVELOPMENT OF VIETNAM, NORTH HUNG YEN BRANCH - Le Thi Thu Thao; Hoang Thi Hong Dao (Journal of Applied Science and Technology, 2019)
The article presents the content of financial appraisal of the loan project at Vietnam Joint Stock Commercial Bank for Investment and Development, Bac Hung Yen branch. The contents of financial appraisal of the loan project at the Branch are illustrated through practical examples. The results showed that the content of the financial aspect of the project at the Branch was carried out in detail and fully by the appraisal officer, but the financial performance evaluation criteria used is not diverse. The appraisal officers should use some other financial evaluation indicators such as breakeven point, benefit cost ratio ... then the financial conclusions will be more comprehensive.